HIV transmission risk among HIV seroconcordant and serodiscordant couples: dyadic processes of partner selection. - Eaton, Lisa A; West, Tessa V; Kenny, David A; Kalichman, Seth C (AIDS and behavior, 2009)
Selecting sex partners of the same HIV status or serosorting is a sexual risk reduction strategy used by many men who have sex with men. However, the effectiveness of serosorting for protection against HIV is potentially limited. We sought to examine how men perceive the protective benefits of factors related to serosorting including beliefs about engaging in serosorting, sexual communication, and perceptions of risk for HIV. Participants were 94 HIV negative seroconcordant (same HIV status) couples, 20 HIV serodiscordant (discrepant HIV status) couples, and 13 HIV positive seroconcordant (same HIV status) couples recruited from a large gay pride festival in the southeastern US. To account for nonindependence found in the couple-level data, we used multilevel modeling which includes dyad in the analysis. Findings demonstrated that participants in seroconcordant relationships were more likely to believe that serosorting reduces concerns for condom use. HIV negative participants in seroconcordant relationships viewed themselves at relatively low risk for HIV transmission even though monogamy within relationships and HIV testing were infrequent. Dyadic analyses demonstrated that partners have a substantial effect on an individual's beliefs and number of unprotected sex partners. We conclude that relationship partners are an important source of influence and, thus, intervening with partners is necessary to reduce HIV transmission risks.
Keywords: Adult; Data Collection; Health Knowledge, Attitudes, Practice; HIV Infections; HIV Seronegativity; HIV Seropositivity; Homosexuality, Male; Humans; Male; Multilevel Analysis; Risk Assessment; Self Disclosure; Sexual Behavior; Sexual Partners; Unsafe Sex